Penerapan Algoritma Advanced Encryption Standard (AES-128) Dengan Mode ECB Dalam Pengamanan File - Simangunsong, Haposan; Raharja, Made Agung (Jurnal Nasional Teknologi Informasi dan Aplikasnya, 2022)
Data Protection is one of the important things to protect, important messages and information from corruption, compromise or loss so that messages and information remain safe. Encryption and decryption techniques are considered to be able to secure data properly by protecting files from being easily read or seen by unauthorized parties. In this case, the authors used a cryptography symmetric algorithm called Advanced Encryption Standard (AES) and Electronic Code Book (ECB) as a solution to existing problems. The AES algorithm process is divided into four steps, the first step is SubBytes, the second step is ShiftRows, the third step is MixColums and the las step is AddRoundKey. And using the SHA algorithm as the hashing function. The algorithm is applied to a web application and using python as a programming language. Advanced Encryption Standard (AES) Algorithm with ECB Mode can be implemented to encrypt and decrypt files. The use of AES will encrypt every 128bit block of the file until it becomes a ciphertext which is an array of encrypted bytes. The decryption process using the AES algorithm with ECB mode will decrypt every 128 bits of the ciphertext to produce the original byte array file. AES with ECB mode which is implemented in the python programming language can be used to encrypt media files such as images, audio and video with a good level of security.